Sexual Sadism Disorder and Coercive Paraphilic Disorder: A Scoping Review. Issue 3 (10th February 2022) - Liu, Alissa; Zhang, Emma; Leroux, Elisabeth J.; Benassi, Paul
ABSTRACT: Background: Valid and reliable diagnostic criteria are essential in forensic psychiatry and sexual medicine due to the severe implications of potential misdiagnoses. One challenge in this field is the poor operationalization of sexual sadism disorder (SSD) and coercive paraphilic disorder (CP+) definitions. Aim: The aim of this scoping literature review is to provide a comprehensive overview of the key conceptual differences between SSD and CP+, as well as consider pragmatic and clinically useful approaches to their diagnostic formulation. Methods: Arksey and O'Malley's methodological framework was followed. A literature search of Medline, PsychInfo, Web of Science, and Cumulative Index to Nursing and Allied Health Literature electronic databases was conducted. Publications in English describing the construct and/or operational definition of SSD or CP+ were included. Full-text studies were reviewed by 2 authors and data was charted and synthesized qualitatively. Results: The initial search provided 1, 271 records, after which 120 full-text papers were considered for eligibility and 48 studies were ultimately included. The most common sources of definitions for SSD and CP+ were the Diagnostic and Statistical Manual of Mental Disorders (n = 53) and the International Classification of Disease (n = 12). There was more variation of terms used for CP+ than SSD. Both CP+ and SSD are critiqued by reviewed literature for having low validity, reliability, and consistency, as well as being conflated with sexual crime. SSD is better described due to having diagnostic criteria and validated diagnostic tools. Clinical Implications: Currently, clinicians rely mostly on the DSM to diagnose SSD or CP+. As applications of SSD and CP+ definitions vary, interpretations may not be generalizable between clinicians. Furthermore, specific diagnoses may be practically unhelpful and unreliable. It may therefore be beneficial for treatment to be determined by risk of harm. In addition to these concerns, the stigma associated with SSD and CP+ may also impact treatment. Strengths & Limitations: Strengths of this study include duplicate review and charting to increase methodological rigor, transparent reporting to minimize publication bias, and encompassing a comprehensive scope. Limitations include the weaknesses of low strength of reviewed literature and risk of publication bias. Conclusion: Despite their significant implications, the definitions of SSD and CP+ are inconsistent and lack reliability. Future research is necessary to develop stronger diagnostic criteria and tools.